The impact of influencers' endorsement on Malaysian young adults' attitudes toward advertising and their purchase intentions - Norshahirah, Binti Abdul Razak (2024)
Social media influencers have significantly altered consumer behavior, particularly among young adults, as they have become more prominent in digital advertising. With more sponsored content and more people being sceptical of influencer endorsement, people are questioning whether or not they are real. The purpose of this study is to investigate the connection between young adults' purchase intentions in Malaysia and their opinions toward influencer endorsements in advertisements. In Malaysia, there is limited research on how influencer endorsements impact their attitudes toward advertising. Rising scepticism about the authenticity of these endorsements, particularly with the increase in sponsored content, challenges their effectiveness. Factors like influencer credibility, compatibility, and perceived authenticity are crucial in determining their impact on consumer behavior, making it important to explore how these elements influence Malaysian young adults' purchase intentions. An online survey was used to gather data from 50 respondents, who were young adults in Malaysia between the ages of 18 and 30, using a quantitative research technique. The association between influencer endorsements' congruence, trustworthiness, and attractiveness and their effect on consumer behavior was assessed statistically. By offering insights into how influencer endorsements can successfully impact purchase decisions, this study adds to the increasing corpus of research on digital marketing and consumer behaviours. It has practical ramifications for marketers looking to increase the success of influencer-driven initiatives in Malaysia's youth market.